A Human Induced Pluripotent Stem Cell−Derived Cardiomyocyte (hiPSC‐CM) Multielectrode Array Assay for Preclinical Cardiac Electrophysiology Safety Screening. Issue 1 (8th December 2015) - Harris, Kate
Abstract: Cardiotoxicity is a leading cause of compound attrition during drug development. Preclinical models used to assess the risk for compound‐induced effects on cardiac electrophysiology largely rely on animals that can differ in terms of sensitivity and specificity to the targeted clinical response. There is currently no in vitro human cardiomyocyte model for routine preclinical compound screening, as adult human cardiac tissue is unsuitable for such screening. The commercial availability of human induced pluripotent stem cell−derived cardiomyocytes (hiPSC‐CMs) makes possible the development of assays for assessing compound‐induced effects on cardiac function in a human cardiomyocyte‐like model. Using multielectrode array (MEA) technology with hiPSC‐CMs provides a facile screen for compound‐induced effects on cardiac electrophysiology. The MEA data generated from hiPSC‐CMs correlate well with the results of conventional preclinical assays and clinical findings. Described in this unit is a technique for measuring extracellular field potentials from hiPSC‐CMs using MEA technology to screen for compound‐induced effects on cardiac electrophysiology. © 2015 by John Wiley & Sons, Inc.